2012
DOI: 10.1186/1471-2407-12-321
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cell cycle regulator CDCA3 promotes oral cancer progression by enhancing cell proliferation with prevention of G1 phase arrest

Abstract: BackgroundCell division cycle associated 3 (CDCA3), part of the Skp1-cullin-F-box (SCF) ubiquitin ligase, refers to a trigger of mitotic entry and mediates destruction of the mitosis inhibitory kinase. Little is known about the relevance of CDCA3 to human malignancy including oral squamous cell carcinoma (OSCC). We aimed to characterize the expression state and function of CDCA3 in OSCC.MethodsWe evaluated CDCA3 mRNA and protein expression in both OSCC-derived cell lines and primary OSCCs and performed functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 37 publications
(36 reference statements)
1
59
0
1
Order By: Relevance
“…Recent studies have demonstrated that the proliferation of cancer is closely correlated to the altered regulation of cell cycles, which might cause uncontrolled growth and contribute to the development and progression of tumor cells [27]. In the present study, our data illustrated that fewer ESCC cells transfected with BANCR siRNA were arrested in the S phage compared to that transfected with NC siRNA (Figure 3 and Figure 4).…”
Section: Bancr Expression Affects the Growth Of Escc Cellssupporting
confidence: 65%
“…Recent studies have demonstrated that the proliferation of cancer is closely correlated to the altered regulation of cell cycles, which might cause uncontrolled growth and contribute to the development and progression of tumor cells [27]. In the present study, our data illustrated that fewer ESCC cells transfected with BANCR siRNA were arrested in the S phage compared to that transfected with NC siRNA (Figure 3 and Figure 4).…”
Section: Bancr Expression Affects the Growth Of Escc Cellssupporting
confidence: 65%
“…To correlate increased expression of these genes with patient outcome, we associated CDC20 and CDCA3 expression levels with survival data and found that patients with higher CDC20 or CDCA3 expression had shorter event-free survival times (Fig-Figure 4 ure 6E and 6F). In support of this observation, CDCA3 over-expression has been associated with poor prognosis in oral cancers by preventing G1 phase arrest [44]. Thus, the identification of a core gene set with periodic regulation across various tissue-types in multiple studies revealed a common epigenetic state in these genes, and uncovered an unexpected association of their expression levels with SETD2 mutation status in kidney tumors that was not reported in previous TCGA analysis.…”
Section: The Core Periodic Genes Have Unique Chromatin Features Thatmentioning
confidence: 61%
“…Because these genes are involved in DNA repair after damage [17], [18] and cell cycle arrest [2], [19], FCM was performed to investigate the effect of FN1BP1 expression on cell cycle in Hep3B cells after the synchronization of nocodazole and UV irradiation. The result of FCM analysis showed that, compared with the non-induced cells, the Dox-induced FN1BP1 over-expression arrested 134±17% of Hep3B cells in the G1 phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some genes ( p21cip1 , ID2 , GMSF , ERCC5, and RPA1 ), which changed in the cDNA microarray analysis, were confirmed by semi-qRT-PCR, and similar changes in expression were observed. According to the Atlas microarray assay, most of these genes were involved in DNA repair after damage [17], [18] and cell-cycle arrest [2], [19]. We performed the cell-cycle analysis using FCM; our results indicated that FN1BP1 over-expression could result in G1 phase arrest.…”
Section: Discussionmentioning
confidence: 96%